Peningkatan Pemahaman Peserta Didik pada Materi Teorema Pythagoras Melalui Pendampingan Belajar Matematika - Yuliany, Nur; Haq, Puji Qur’ani Al; Nuhdia; Aulliani, Irma (Faculty of Tarbiyah and Teacher Training, 2026)
The Pythagorean Theorem explains the relationship between the sides of a right triangle, which is relevant in everyday life. Students' difficulties in solving problems related to the Pythagorean Theorem remain moderate to high, with limited teaching methods and a lack of individual guidance from teachers contributing to challenges in improving students' understanding. Therefore, a community service activity was conducted in the form of mathematics learning assistance. This activity aimed to enhance students' understanding of the Pythagorean Theorem through mathematics learning assistance at MTs Ash-Shalihin, Gowa Regency. The assistance was carried out using a collaborative approach, lectures, discussions, and practical demonstrations of the theorem using grid paper. The results showed a significant improvement in students' understanding, with the majority achieving high and very high learning outcomes. Individualized approaches and interactive learning motivated students and helped them maintain focus. This study highlights the importance of structured learning assistance in supporting the success of geometry education. Future research is recommended to integrate technology and explore its impact on other aspects, such as motivation and critical thinking skills.